The role of honey, curcuma, and black cumin supplements in overcoming stunting on the adaptive immune system - Cecep Sabarudin; Patonah Hasimun; Herni Kusriani; Ahmad Azrul Zuniarto; Siti Pandanwangi; Eva Fatmawati; Arief R. Afief; Jajang Japar Sodik (Institute of Computer Science (IOCS), 2025)
Stunting is strongly associated with impaired immune function, as chronically malnourished children tend to have weaker immunity and are more vulnerable to infection. This study aimed to examine the effect of temulawak–black cumin herbal honey on the adaptive immune system in stunted children. A quasi-experimental one-group pre-test and post-test design was used. The findings showed that the intervention significantly increased height-for-age (TB/U) in the treatment group compared to the control group (p = 0.014). Weight-for-age (BB/U) also rose significantly within the treatment group (p = 0.013), but no significant difference was found relative to the control group (p = 0.192). The supplement significantly elevated IgM levels in the treatment group (p = 0.001), though again without a significant difference from the control (p = 0.546). CD4 concentration decreased in the treatment group (p = 0.003), but the change was not significantly different from the control (p = 0.682). In conclusion, temulawak–black cumin herbal honey can improve nutritional status and enhance adaptive immunity by increasing IgM levels, although it does not raise CD4 levels and instead slows CD4 decline. However, its effectiveness in increasing IgM and CD4 concentrations compared to controls is not significant.